2016
DOI: 10.1021/jacs.6b00468
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Trapped Tetrahedral Cages via Alkyne Metathesis

Abstract: In dynamic covalent synthesis, kinetic traps are perceived as disadvantageous, hindering the system from reaching its thermodynamic equilibrium. Here we present the near-quantitative preparation of tetrahedral cages from simple tritopic precursors using alkyne metathesis. While the cages are the presumed thermodynamic sink, we experimentally demonstrate that the products no longer exchange their vertices once they have formed. The example reported here illustrates that kinetically trapped products may facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 45 publications
5
103
0
3
Order By: Relevance
“…In principle, abolition of one hydrogen bond by deprotonation might be expected to lead to loss of that monomer unit from the capsule, but the enthalpic cost of rupturing additional H-bonds would be very large. This reinforcement of weak interactions by geometrical constraints is reminiscent of that observed in other systems such as the trefoil knot reported by one of us46 and Moore's recent kinetically-trapped tetrahedral cages47.…”
Section: Resultssupporting
confidence: 64%
“…In principle, abolition of one hydrogen bond by deprotonation might be expected to lead to loss of that monomer unit from the capsule, but the enthalpic cost of rupturing additional H-bonds would be very large. This reinforcement of weak interactions by geometrical constraints is reminiscent of that observed in other systems such as the trefoil knot reported by one of us46 and Moore's recent kinetically-trapped tetrahedral cages47.…”
Section: Resultssupporting
confidence: 64%
“…Fujita describes this type of phenomenon as "emergent behaviour" 34 and it is clear that this can also thwart attempts at the topological design of organic cage materials. Further complicating the matter, there are some reports of the kinetic trapping of products 26 or of solvent choice influencing the topological outcome; in an example from Liu and Warmuth, where they reacted a tetraformylcavitand with ethylene diamine in an imine condensation reaction, it was found that changing between tetrahydrofuran, chloroform and dichloromethane as the solvent could change the dominant product from a [4 + 8] cage, to a [6 + 12] octahedron to a [8 + 16] square antiprism. 35 As the majority of organic cages are formed by reversible dynamic covalent chemistry (DCC), the product distribution Fig.…”
Section: Topological Control?mentioning
confidence: 99%
“…Fig. 2 An example of how two porous organic cages that both have an underlying topology of a tetrahedron adopt different geometric shapes, in one case maintaining a tetrahedron shape 26 (right hand side), and in the other adopting an octahedral shape (left hand side). 27 The underlying topologies are shown in purple and the geometric shapes in orange.…”
Section: Topological Control?mentioning
confidence: 99%
See 1 more Smart Citation
“…[110][111][112][113][114] Da die C-C-Bindungsknüpfung in diesem Fall nur in Gegenwart eines Katalysators reversibel ist, sind solche Ansätze besonders fürd ie Synthese von stabilen Käfigen interessant. Alkinmetathese wurde in einigen Beispielen für die Synthese von formgetreuen molekularen Käfigen genutzt.…”
Section: Dynamisch-kovalente Reaktionenunclassified